Market perception of bank risk and securitization in Spain - Iglesias-Casal, Ana; López-Penabad, Maria Celia; López-Andión, Carmen; Maside-Sanfiz, Jose Manuel (Journal of Business Economics and Management, 2016)
This paper examines the systematic risk in those banks that participated as issuers of securitization transactions in the Spanish market. Using event study methodol- ogy and allowing systematic risk to change gradually within the event window, this paper provides empirical evidence that securitization has a positive impact on Spanish bank's systematic risk (beta) from the beginning to the end of the event window. Additionally, we assess how much of the beta effect is due to volatility and how much to market cor- relation. The increase in beta is solely due to an increase in banks’ correlations, improving portfolio diversification. The empirical results presented in this paper show important informative implications for the different agents related to banks. This creates a challenge for financial regulation, which has typically focused on individual institutions.